Biosynthesis of Tyrosine Hydroxylase in Rat Adrenal Medulla after Exposure to Cold - Chuang, De-Maw (1974)
Exposure of rats to cold increases the content of tyrosine hydroxylase [EC 1.14.16.2; L-tyrosine, tetrahydropteridine:oxygen oxidoreductase (3-hydroxylating)] in adrenal medulla, causing a long-lasting enhancement of the enzymatic activity. We have used an antibody specific to tyrosine hydroxylase to study the molecular mechanisms involved in the trans-synaptic induction of adrenal tyrosine hydroxylase. The rate of [(3)H]-leucine incorporation into adrenal tyrosine hydroxylase was measured by specific immunoprecipitation at various times after exposure to cold (4 hr). This enhanced rate of incorporation was evident between 11 and 30 hr after the beginning of exposure to cold, but not at 7 and 50 hr. The increase of (3)H incorporation preceded the maximal enhancement of adrenal tyrosine hydroxylase activity, which occurred about 30 hr after stimulation. Neither the activity of tyrosine hydroxylase nor the rate of (3)H incorporation into tyrosine hydroxylase in cervical sympathetic ganglia was changed by 4 hr of exposure to cold. The rate of degradation of tyrosine hydroxylase was estimated at 26 and 50 hr after the beginning of cold stress, as determined by the technique of double-isotope labeling. The data indicate that the tyrosine hydroxylase degradation rate was not reduced by exposure to cold. Thus, the induction of adrenal tyrosine hydroxylase appears to be due to an increased rate of its synthesis.